Dlaczego Jezus był ze zwierzętami (Mk 1,13)? Odniesienia do zwierząt w Ewangelii Markowej - Malina, Artur (Verbum Vitae, 2017)
Jesus’ being with the wild beasts in the desert during His temptations is mentioned only in the Gospel of Mark (1:13). His victory over Satan is confirmed by the state of peaceful harmony with the nature surrounding Him, and by the service of the angels to Him. Several other references to animals in Mark emphasize the reality of God’s saving activity offered to men and women in the midst of their real, everyday condition and needs. All of this gospel's references to the beasts serve as examples of this kind of immediacy and reality, whether reported indirectly or directly, and whether understood literally or figuratively.